The Role of Artificial Intelligence in Advancing Sustainable Banking and Service Efficiency in Nigerian Financial Institutions: An Assessment of Selected Quoted Banks - Ogundele, Abiodun Thomas; Ibitoye, Olusola Anthony; Akinterinwa, Oluwatoyin Olusola; Adeniran, Abraham; Ibukun, Felix Olusegun; Apata , Temitope Gift (Journal of Sustainable Development Law and Policy, 2025)
The rapid growth of human reasoning impacts the sustainability and efficiency of the banking industry globally, including in Nigeria. Many banks have used technology and creativity to improve service efficiency and revenue sustainability due to worries about the detrimental effects of human intelligence. Our research analyses how AI integration influences sustainable banking and service efficiency in selected Nigerian listed banks. Natural language processing, machine learning, and predictive analytics are revolutionising banking. In addition, risk management, fraud detection, customer service, and operational automation applications create data privacy, ethical, and regulatory compliance issues, though they are efficient and cost-effective. According to a cross-sectional study of clients from five Nigerian deposit money banks: Access Bank Plc, Fidelity Bank Plc, First Bank Plc, Guarantee Trust Bank Plc, and Zenith Bank Plc, 384 individuals completed the self-administered questionnaire SAQ. In this study, the following methods were used: mean, standard deviation, skewness, kurtosis, Jarque Bera, correlational analysis, and OLS regression. The researchers observed that AI awareness, application, and effectiveness have an impact on the service efficiency of a subset of Nigerian quoted deposit money banks. Finance firms in Nigeria use AI to improve productivity and client happiness as one suggestion was to automate tedious tasks for bank services. However, government regulations restrict Nigerian banks’ AI usage. To bridge these gaps, the paper recommends banking AI regulations, infrastructural development, education, training, and monitoring. The paper also recommends that Nigerian officials automate identity verification and risk assessment to speed up procedures. Overall, there should be strong sustainability, security, and privacy laws to promote economic and social objectives.